Deontology defended - Heinzelmann, Nora (Synthese, 2018)
Empirical research into moral decision-making is often taken to have normative implications. For instance, in his recent book, Greene (2013) relies on empirical findings to establish utilitarianism as a superior normative ethical theory. Kantian ethics, and deontological ethics more generally, is a rival view that Greene attacks. At the heart of Greene’s argument against deontology is the claim that deontological moral judgments are the product of certain emotions and not of reason. Deontological ethics is a mere rationalization of these emotions. Accordingly Greene maintains that deontology should be abandoned. This paper is a defense of deontological ethical theory. It argues that Greene’s argument against deontology needs further support. Greene’s empirical evidence is open to alternative interpretations. In particular, it is not clear that Greene’s characterization of alarm-like emotions that are relative to culture and personal experience is empirically tenable. Moreover, it is implausible that such emotions produce specifically deontological judgments. A rival sentimentalist view, according to which all moral judgments are determined by emotion, is at least as plausible given the empirical evidence and independently supported by philosophical theory. I therefore call for an improvement of Greene’s argument.
Gesehen am 27.01.2025